Pengaruh Penerapan Metode Iqro Terhadap Kemampuan Membaca Al-Qur’an Pada Peserta Didik (Studi Survey di TPA Al-Furqon) - Tiara Nabila Putri; Yuyu Wahyudin; Firdaus Suhaimy (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effect of implementing the Iqro Method on students’ Qur’an reading ability at TPA Al-Furqon, using a quantitative approach with a survey design. The research population consisted of all students in classes V A and VI B, totaling 35 students, who were also used as the sample. Data were collected through observation, questionnaires, and achievement tests, and analyzed using the Product Moment correlation with the assistance of SPSS 26 software. The results indicated a significant effect of the Iqro Method on students’ Qur’an reading ability, with a correlation coefficient of 0.649. The contribution of the Iqro Method to Qur’an reading ability was 42%, while the remaining 58% was influenced by external factors such as motivation, family environment, and the availability of learning media. Therefore, it can be concluded that the implementation of the Iqro Method is effective in improving students’ Qur’an reading ability, although its success is still influenced by supporting factors.